Energy density functional and sensitivity of energies of giant resonances to bulk nuclear matter properties - S. Shlomo; A. I. Sanzhur (Ядерна фізика та енергетика)
We provide a short review of the current status of the nuclear energy density functional (EDF) and the theoretical results obtained for properties of nuclei and nuclear matter. We will first describe a method for determining the parameters of the EDF, associated with the Skyrme type effective interaction, by carrying out a Hartree - Fock (HF)-based fit to the extensive set of data of ground-state properties and constraints. Next, we will describe the fully self-consistent HF-based random-phase-approximation (RPA) theory for calculating the strength functions S(E) and centroid energies ECEN of giant resonances and the folding model (FM) distorted wave Вorn approximation (DWBA) to calculate the excitation cross-section of giant resonances by α scattering. Then we will provide results for: (i) the Skyrme parameters of the KDE0v1 EDF; (ii) consequences of violation of self-consistency in HF-based RPA; (iii) FM-DWBA calculation of excitation cross-section; (iv) values of the ECEN of isoscalar and isovector giant resonances of multipolarities L = 0 – 3 for a wide range of spherical nuclei, using 33 EDFs associated with the standard form of the Skyrme type interactions, commonly employed in the literature; and (v) the sensitivities ECEN of the giant resonances to bulk properties of nuclear matter (NM). We also determine constraints on NM properties, such as the incompressibility coefficient and effective mass, by comparing with experimental data on ECEN of giant resonances.